New Drug Trends across Welsh Prisons: Evaluating the Role of People with Lived Experience of Substance Misuse and Supporting their Recovery - M. Vigar; C. Watkins; J. Clifford; M. Jones (Emerging Trends in Drugs, Addictions, and Health)
Introduction: This presentation will cover two areas of work. Firstly, we will provide a summary of the current trends of substance misuse across prisons in South Wales, where novel psychoactive substances continue to be widely used, including the market value for these substances in the prison system. The second element of the presentation will share the findings of our research in the attempt to better understand the lived experience of those affected and provide a more informed support and intervention to other prisoners. Methods: The analysis of trends across Welsh prisons will utilise data from the following sources: Mandatory Drug Test results, drug testing sample data from WEDINOS, prison data on drug finds, intelligence reports and substance misuse observation records being opened. The research into prisoner peer mentoring will utilise standardised interviews with both prisoners with lived experience providing support, and prisoners receiving support. The standardised interviews will aim to identify consistent themes, proposals for good practice and wider mainstream implementation. Results: Early data shows a significant prevalence of Synthetic Cannabinoids and the emergence of new trends related to the consumption of Synthetic Opioids. Conclusions: More attention should be paid to the diffusion on NPS in prison settings. Full results of our investigation will be available and be discussed at the time of the conference.